2008
DOI: 10.1128/mcb.01489-07
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signals Regulate Rapid Coactivator Recruitment at AP-1 Sites by Altered Phosphorylation of both CREB Binding Protein and c-jun

Abstract: Retinoic acid (RA) inhibits matrix metalloproteinase 9 (MMP-9) expression due to AP-1 inhibition resulting from retinoic acid receptors (RARs) competing for limiting amounts of coactivator proteins. However, given the rapid kinetics of MMP-9 transcription, it seems unlikely that these interactions can be explained passively. Our previous studies indicated that coactivator and transcription factor phosphorylation may allow for rapid regulation of MMP-9 expression. In the present study we tested this hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
1
19
1
Order By: Relevance
“…In contrast with previous reports showing regulation of MMP-9 expression by CREB and its cofactors in nonneuronal cells (47,48), our data indicate that in neurons BDNF-induced MMP-9 transcription is not mediated by CREB activity. However, as already mentioned, MMP-9 gene expression seems to be modulated in a cell type/stimulus-specific manner.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In contrast with previous reports showing regulation of MMP-9 expression by CREB and its cofactors in nonneuronal cells (47,48), our data indicate that in neurons BDNF-induced MMP-9 transcription is not mediated by CREB activity. However, as already mentioned, MMP-9 gene expression seems to be modulated in a cell type/stimulus-specific manner.…”
Section: Discussioncontrasting
confidence: 55%
“…As in nonneuronal cells, MMP-9 transcription has been shown to be regulated by another transcription factor, the cAMP response element binding protein (CREB) and its coactivators CREB binding protein (CBP) and p300 (47,48); we verified whether CREB contributes to BDNF-mediated MMP-9 transcription in neurons. We used two different approaches to inhibit endogenous CREB in neurons: we overexpressed inducible cyclic AMP early repressor 2ā„ (ICER IIā„) (35), which is an endogenous repressor of CREB, or a mutant form of CREB (A-CREB) that inhibits DNA binding of endogenous CREB (34).…”
Section: Resultsmentioning
confidence: 89%
“…CBP as an important transcription co-activator not only regulates transcriptional factor DNA binding, but also can intervene their transcriptional activity (Goodman et al, 2000;Arany et al, 1994). At last, many various transcriptional factors competition for limiting amounts of CBP (Zhao et al, 2011;Ramos et al, 2010;Tsai et al, 2008;Du et al, 2014;Rajendran et al, 2013), which is still an important research problem.…”
Section: Discussionmentioning
confidence: 98%
“…It functions as a co-activator of DNA binding, regulating the activity of different transcriptional factors, including activator protein-1 (AP-1), nuclear factor kappaB (NF-ĪŗB) and CREB (Zhao et al, 2011;Ramos et al, 2010;Tsai et al, 2008;Du et al, 2014). Among these transcriptional factors, AP-1 is known as a key mediator in MI/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…AP-1 is a universally expressed transcription factor known to exert a wide range of effects on the vasculature. 30 Several independent investigations have suggested that AP-1 may enlist the help of epigenetic factors, such as CREB binding protein, 31 PCAF (p300/CBP associated factor), 32 and Brahma-related gene 1, 33 to activate transcription. The finding that AP-1 may rely on SET1-dependent H3K4 methylation to activate endothelin-1 transcription reinforces the assertion that epigenetic factors play essential roles in transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%